PERSIAPAN PRA PERNIKAHAN SEBAGAI FONDASI KEHARMONISAN KELUARGA: TINJAUAN PSIKOLOGI KELUARGA BERBASIS STUDI LITERATUR - Shofiyah Shofiyah (Jurnal Keluarga Sehat Sejahtera, 2025)
This article aims to discuss premarital preparation as the foundation for harmony in a family. Marriage is not only the union of two individuals, but also the meeting of two personalities, two values, and two life journeys. Behind the happiness of marriage lies a long process that requires emotional, mental, and spiritual readiness. This article also reviews premarital preparation as the foundation for family harmony from a family psychology perspective, focusing on four main aspects: emotional commitment, financial management, reproductive health, and readiness for pregnancy. This study uses a descriptive qualitative research method based on literature review, examining family psychology theories and research results related to premarital counseling and family health, as well as books related to both. The results of this study show that these four aspects are interrelated and form a system of balance in the household. Through the perspective of family psychology, premarital preparation can be understood as a process of developing self-awareness, empathy, and adaptability in building a stable, warm, and sustainable family relationship.